PERAN PERWAKILAN DIPLOMATIK DALAM MELINDUNGI TERPIDANA ANAK INDONESIA DI LUAR NEGERI (STUDI KASUS TERPIDANA ANAK INDONESIA ALI YASMIN DI AUSTRALIA) - Laras Hani Novianty (BELLI AC PACIS (Jurnal Hukum Internasional), 2023)
The imprisonment of minors in adult prison cells is an act that violates the human rights of the child, because children have different vulnerabilities and circumstances than adults. The Australian Government's action to imprison Indonesian migrant smugglers who are partly children in adult prisons is a violation of a human rights values. The method used in this study is a normative prescriptive method that aims to analyze how protection is carried out by the Government of Indonesia through its representatives abroad protecting the citizens of Indonesia. The conclusion of this study showed that the imprisonment of children violates various international conventions namely, the Convention on the Rights of the Child and ICCPR. Protection of Indonesian citizens abroad is regulated in The Minister of Foreign Affairs regulation of the Republic of Indonesia No. 5 of 2018. Protection is carried out within the corridors of international law and not ignoring the applicable laws in Australia.